A cross-sectional survey study on the use of communication methods in the dentist-geriatric patient relationship - Emine Pirim Görgün; Kübra Güler (Cumhuriyet University, 2022)
According to the data the World Health Organization (WHO) provides, the population has been aging more rapidly than in the past, and it has been reported that the number of people over the age of 60 exceeds the number of children under the age of 5. This demographic change has forced countries to plan their health systems with the aging population in mind. In this cross-sectional study, we aimed to see and evaluate the attitudes of dentists and trainee dentists towards communication with patients they describe as "elderly" during their examination and treatment. This study applied a 25-item questionnaire on dentist-geriatric patient communication to 168 trainee dentists and 73 dentists in our faculty, including 4th and 5th-year students, residents, and faculty members. Sixteen items, the first 7 of which are "basic", include questions that examine the methods recommended by the American Medical Association in physician-patient communication and whether they find these methods effective. The data were analyzed using the SPSS 23.0, and a p-value of 0.05 is used as the cutoff for significance. Dentists routinely use an average of 4.6 of the 16 methods and 2.5 of the seven basic methods. While the most frequently used methods were "speaking slowly" and "using a simple language", the least was "using videos". Health literacy awareness and outcome expectancy were associated with the number of methods used. The number of routine use of the methods is quite low among dentists and trainee dentists. It has been observed that communication methods that would be effective in relationships with geriatric patients with low health literacy skills are not routinely used. It has been concluded that the communication methods that can be used effectively for communication with geriatric patients should be embedded into the dental curriculum.